Regional Collective Action Wraps Up - Longley, K.; Otieno, Y.; Katingi, E.; Seré Rabé, Carlos; Sirengo, R. (2011)
After four years, the Regional Collective Action Programme has come to an end. In this final issue of Collective Action News, we report on how Regional Collective Action activities have supported the work of the Consortium and the CRPs. The Regional Collective Action Programme has been described by Carlos Seré, Director General of the International Livestock Research Institute (ILRI), which has hosted the Programme since its inception in 2007, as ‘a bold experiment that achieved considerable success in promoting collaborative action in eastern and southern Africa that has now been overtaken by the process of CGIAR reform’. Many of the activities started under the Programme have now been incorporated into the CGIAR Consortium and the CGIAR Research Programmes (CRPs).